The impact of climate change on the effectiveness of water conservation policies in western Kansas and the Ogallala aquifer - Garay Armoa, Pedro Vicente (Kansas State University, 2015)
Water scarcity is already a critical issue in many regions across the world and in many places water supplies are likely to be further threatened by climate change (Bates et al., 2008). Climate change will affect water availability in these areas both directly and indirectly. The direct effects come about because increased temperature (accompanied by changes in wind, humidity, and solar radiation) may increase evaporative losses from surface water bodies, and also because reduced precipitation lowers the rate of water inflows. In the case of groundwater, these factors will reduce the rate of aquifer recharge (Bates et al., 2008). The indirect effects arise from the biophysical impacts of climate change on vegetation, which are induced from rising temperatures, changing precipitation regimes, and increased atmospheric carbon dioxide levels. As a result of climate change, significant changes are expected in the hydrological cycle. This research is focused in how climate change can affect crop, land, and water allocation over time. The specific issue of this research comes from the following question: Is climate change likely to have a significant impact on the effectiveness of different water conservation policies in the High Plains aquifer region? This study is focused on the American High Plains, one of the most important water-scarce agricultural regions in North America. The study region for this research is a 31-county area overlying the Ogallala aquifer in western Kansas. This region encompasses approximately the western third of Kansas. Across these counties, the estimated remaining usable lifetime for aquifer water ranges from 50 to over 200 years (KGS), representing the range of water available in various parts of the aquifer. A Positive Mathematical Programming (PMP) model (Howitt, 1995) was developed and calibrated to land- and water-use data in the thirty one county area for a base period of 2000-2008. The PMP simulation uses inputs of price conditions and the aquifer level in a given year to predict the acreages planted to each of the major crops and the water use by crop. Decision makers are assumed to maximize profits, given the limited availability of water and arable land. The major crops in the model include wheat, corn, sorghum, soybeans, and alfalfa; the vast majority of historical planted acreage in the case counties is comprised of these five crops. The model was run for each of the case regions after calibrating the PMP model to data from 2000-2008. Calibration ensures that the model predictions fall within a small tolerance of the base period observations. This step avoids the problem of over-specialization (where the model places all of the acreages under one or two of the most profitable crops), and gives realistic acres and water use figures with which to work. The results suggest that the effects of the use of water conservation policies such as water use restriction and permanent conversion to dryland crops have positive effects on the trends of the different variables studied. With the implementation of these two policies, lower levels of total water use and higher levels of saturated thickness result but with a consequence of lower levels of net returns. However, the positive effects are lower in almost all cases if the effects of climate change on the same policies are taken into consideration. The scenarios of higher levels of temperature and lower precipitation levels projected for the region imply a greater demand for water for irrigated crops that results in lower levels of saturated thickness and simultaneously lower levels of net returns.
Keywords: Climate change; Water conservation; Natural Resource Management (0528)